HUBUNGAN KEKUATAN OTOT LENGAN DAN KOORDINASI MATA TANGAN DENGAN KEMAMPUAN SERVIS PANJANG PEMAIN BULUTANGKIS PB WARDAH - Ali Mardius; Apriyanti Rahmalia; Jefri Rizwar; Meiriani Armen (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
Abtract The problem in this study is the low long service ability of badminton player PB Wardah. The low ability to serve long is influenced by several factors, such as arm muscle strength and hand eye coordination. The purpose of this study was to determine the relationship between arm muscle strength and hand eye coordination with the long serve ability of badminton player PB Wardah. This type of study is correlational. A total of 30 male badminton players PB Wardah were used as research samples, who were recruited using purposive sampling technique. The arm muscle strength instrument uses a push-up test for 1 minute, eye-hand coordination uses a tennis ball throw and catch test, and long service ability uses a long serve test. Data were analyzed by simple and multiple correlation techniques α = 0.05. The results of hypothesis testing show: (1) there is a significant relationship between arm muscle strength and long service ability (tcount = 5.492 > ttable = 2.048), (2) there is a significant relationship between hand eye coordination and long service ability (tcount = 3.084 > ttable = 2.048), and (3) there is a significant relationship between arm muscle strength and hand eye coordination together with long service ability (Fcount = 26.814 > Ftable = 3.354). In conclusion, if badminton player PB Wardah wants to improve his long serve ability, he must have good arm muscle strength and eye-hand coordination. Keywords: Arm Muscle Strength, Hand Eye Coordination, Badminton Long Serve